Configuración de una estructura de contención para optimizar la usabilidad del dispositivo de medición de gases por desplazamiento de líquido GASLIQ, con énfasis en las funciones prácticas, comunicativas y estéticas (2024)
Measurements of gas flows can be carried out with the support of numerous known instruments such as meters, counters or flow indicators (Badger Meter, 2020), under various methods such as the displacement of liquids. According to Sanabria et al. (2012), the simplicity and low cost of this technique make it one of the most accepted for measuring light gases such as methane, which is occurs after the decomposition of organic matter. So then, it is possible to find a great variety of gas measuring instruments with technological differentials designed for measurement, either on a laboratory scale or on an industrial level.